Pengaruh Literasi Keuangan Dalam Penggunaan Financial Technology (Fintech) Terhadap Perilaku Manajemen Keuangan Dikalangan Masyarakat UMKM Kota Medan - Simanjuntak, David Renaldi; Berampuh, Rahmawati S.; Sukma, Yeni Ariesa, STIM (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study takes a quantitative approach using a quantitative descriptive type. The population of this study is 1,966 members of the MSME community who have been verified and are under the guidance of the Medan City Trade & Industry SME Cooperative Service, with a sample of 332 based on the Slovin formula. In conducting statistical tests, researchers used 100 respondents outside the research sample. The results of statistical tests explain that the financial literacy and financial technology variables, both simultaneously and partially, have an impact on financial management behavior with a coefficient of determination level of 0.258. This explains that financial literacy and financial technology have an impact of 25.8% on financial management behavior. However, the difference of 74.2% is influenced by variables outside this study.